2015
DOI: 10.1111/1742-6723.12367
|View full text |Cite
|
Sign up to set email alerts
|

Review article: Emergency department models of care in the context of care quality and cost: A systematic review

Abstract: To identify current ED models of care and their impact on care quality, care effectiveness, and cost. A systematic search of key health databases (Medline, CINAHL, Cochrane, EMbase) was conducted to identify literature on ED models of care. Additionally, a focused review of the contents of 11 international and national emergency medicine, nursing and health economic journals (published between 2010 and 2013) was undertaken with snowball identification of references of the most recent and relevant papers. Artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 62 publications
1
54
1
4
Order By: Relevance
“…Moreover, it should be considered in studies and decision-makings that access to ED is an issue at a strategic government level, whereas throughput efficiencies are being addressed at a local operational level. [51]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it should be considered in studies and decision-makings that access to ED is an issue at a strategic government level, whereas throughput efficiencies are being addressed at a local operational level. [51]…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have shown that these units can effectively reduce mortality, the LOS, and access block, as well as improve staff and patient satisfaction. [51]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With high fixed workforce costs (ie, salary and wages) and small marginal costs (ie, consumables, pathology, and radiology), ED budgets had been historically average cost based, aggregated, and capped with adjustments calculated as the additional workforce (ie, inputs) required to meet rising demand. This is reflected in the considerable variation in how specific EDs value their available resources with many different models of care reported in the literature …”
Section: Introductionmentioning
confidence: 99%
“…Due to considerations of space, this paper cannot provide a comprehensive review of existing models. A recent review discusses ED models of care in the context of care quality, care effectiveness, and cost (Wylie et al, 2015).…”
Section: Ed Crowding Problemmentioning
confidence: 99%